2011
DOI: 10.1007/s10897-011-9364-y
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Values of Maternal Serum Analytes in Second Trimester Screening: Looking Beyond Trisomy and NTD's

Abstract: Second trimester maternal serum screening can identify high risk pregnancies and fetuses at risk for birth defects (in addition to those in the standard interpretation). The purpose of this study was to quantify such risks to improve counseling. We compared outcomes of 692 pregnancies that had abnormal levels of at least one analyte with a cohort of 713 pregnancies with normal analytes. Increased risks include: demise with high AFP and low uE3; intrauterine growth restriction with high AFP, high and low hCG, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…In the absence of fetal chromosomal or structural anomalies, mid-trimester ms-AFP levels >2.5 MoM are thought to reflect a defect in placentation [placental abruption, placenta previa, abnormal placental adherence (placenta accreta, increta and percreta)] (3, 36, 37). They also associated with an increased risk for pregnancy complications including: late fetal loss [OR 10.1 (95% CI: 7.5-13.5)], gestational hypertension [OR 1.6 (95% CI: 1.3-2.1)], preeclampsia [OR 0.83 (95% CI: 0.44–1.56)], IUGR [OR 2.3 (95% CI: 1.8-2.9)], preterm delivery [OR 1.8 (95% CI: 1.5-2.3)] and IUFD [OR 5.3 (95% CI: 3.8-7.3)] (3, 4, 17, 23-25, 38, 39). Mechanisms for elevated mid-trimester ms-AFP levels with a structurally normal fetus include: disruption of the fetal-maternal placental barrier, placental vascular damage from early abruption, fetal-maternal bleeding and fetal-placental ischemia (3, 36, 40-42).…”
Section: Evidence Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of fetal chromosomal or structural anomalies, mid-trimester ms-AFP levels >2.5 MoM are thought to reflect a defect in placentation [placental abruption, placenta previa, abnormal placental adherence (placenta accreta, increta and percreta)] (3, 36, 37). They also associated with an increased risk for pregnancy complications including: late fetal loss [OR 10.1 (95% CI: 7.5-13.5)], gestational hypertension [OR 1.6 (95% CI: 1.3-2.1)], preeclampsia [OR 0.83 (95% CI: 0.44–1.56)], IUGR [OR 2.3 (95% CI: 1.8-2.9)], preterm delivery [OR 1.8 (95% CI: 1.5-2.3)] and IUFD [OR 5.3 (95% CI: 3.8-7.3)] (3, 4, 17, 23-25, 38, 39). Mechanisms for elevated mid-trimester ms-AFP levels with a structurally normal fetus include: disruption of the fetal-maternal placental barrier, placental vascular damage from early abruption, fetal-maternal bleeding and fetal-placental ischemia (3, 36, 40-42).…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…The risk for adverse pregnancy outcome also increases as mid-trimester ms-hCG and/or ms-AFP levels become more extreme. In the absence of fetal chromosomal or structural anomalies, combined mid-trimester elevation in ms-hCG and ms-AFP levels suggest a more complex type of placental pathology which have stronger association with pregnancy complications including: late fetal loss [OR 7.05 (95% CI: 1.18-29.88)], gestational hypertension [OR 0.78 (95% CI: 0.13-3.24)], preeclampsia [OR 6.67 (95% CI: 3.84-11.58)], IUGR [OR 3.54 (95% CI: 1.26-9.14)], preterm delivery [OR 3.20 (95% CI: 1.49-6.61)] and IUFD [OR 6.87 (95% CI: 1.71-22.93)] (3, 4, 23-25, 39, 46, 47). Placental pathology studies suggest that unexplained combined mid-trimester elevation in ms-hCG and ms-AFP levels associated with villitis and placental vascular lesions (48).…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…More recent studies have also confirmed these findings [5,[9][10][11]. However, studies by Smith and McPhearson showed no significant increase in IUGR with an elevated AFP [4,12].…”
Section: Introductionmentioning
confidence: 79%
“…İkinci trimesterde saptanan yüksek MSAFP değerlerini açıklayacak her hangi bir patolojinin bulunmadığı gebeliklerin yaklaşık %25'inde ilerleyen gebelik dönemlerinde çeşitli komplikasyonlar görüldüğü bildirilmiştir (21). Yüksek MSAFP değeri ile birlikte diğer belirteçlerden birinin de artmış düzeyde saptanması daha fazla oranda kötü gebelik prognozu ile ilişkilidir (22,23). Çalışmamızda da yüksek MSAFP saptanan olgular içerisinde NTD saptanmayanların bir kısmında AFP yüksekliğini açıklayacak fetal anomaliler tespit edilmişken bir bölümünde ise ilerleyen gebelik haftalarında çeşitli komplikasyonlar izlenmiştir.…”
Section: Discussionunclassified